The role of Tax Planning to benefit from tax incentives linked to corporate income tax –Case study on Algerian economic institutions over the period 2012-2018 - Mimoune, Imad rachid; Oualhi, Boualam (Journal of Research in Finance and Accounting, 2026)
This paper aims to examine the most important aspects of tax planning that result in the exploitation of tax incentives for corporate profits to expand investment, by examining and analyzing financial statement of a group of Algerian economic institutions under study during 2012-2018. The study concluded that companies set Tax planning as one of their top priorities to reduce corporate income tax rate, while the investments that were created have nothing to do with the decrease noted on the amounts of taxes due to the profits of the companies.